(untitled) (Journal of International English Research Studies (JIERS), ISSN: 3048-5231, 2025)
After 2001 Gujarat Earthquake and 2005 Kashmir Earthquake, there is a nation-wide attention to the seismic vulnerability assessment of existing buildings. There are many literatures available on the seismic evaluation procedures of multi-storeyed buildings using nonlinear static (pushover) analysis. There is no much effort available in literature for seismic evaluation of existing bridges although bridge is a very important structure in any country. There are presently no comprehensive guidelines to assist the practicing structural engineer to evaluate existing bridges and suggest design and retrofit schemes. In order to address this problem, the aims of the present project was to carry out a seismic evaluation case study for an existing RC bridge using nonlinear static (pushover) analysis. Bridges extends horizontally with its two ends restrained and that makes the dynamic characteristics of bridges different from building. Modal analysis of a 3D bridge model reveals that it has many closely-spaced modes. Participating mass ratio for the higher modes is very high. Therefore, pushover analysis with single load pattern may not yield correct results for a bridge model. A 12-span existing RC bridge was selected for the case study. Standard pushover analysis using FEMA 356 (2000) displacement coefficient method and an improved upper bound pushover analysis method were used to analyse the building. Some of the analysis parameters were suitably modified to use in a bridge structure. The evaluation results presented here shows that the selected bridge does not have the capacity to meet any of the desired performance level.